Offline System for 2D Indoor Navigation Utilizing Advanced Data Structures - Jorge Luis Veloz; Leo Sebastián Intriago; Jean Carlos Palma; Andrea Katherine Alcívar-Cedeño; Álvaro Antón-Sacho; Pablo Fernández-Arias; Edwan Anderson Ariza; Diego Vergara (Informatics, 2025)
This study introduces a robust offline system for 2D indoor navigation, developed to address common challenges such as complex layouts and connectivity constraints in diverse environments. The system leverages advanced spatial modeling techniques to optimize pathfinding and resource efficiency. Utilizing a structured development process, the proposed solution integrates lightweight data structures and modular components to minimize computational load and enhance scalability. Experimental validation involved a comparative approach: traditional navigation methods were assessed against the proposed system, focusing on usability, search efficiency, and user satisfaction. The results demonstrate that the offline system significantly improves navigation performance and user experience, particularly in environments with limited connectivity. By providing intuitive navigation tools and seamless offline operation, the system enhances accessibility for users in educational and other complex settings. Future work aims to extend this approach to incorporate additional features, such as dynamic adaptability and expanded application in sectors like healthcare and public services.